Morfoanatomia foliar de duas espécies endêmicas da Chapada Diamantina, Ba, Brasil: Pouteria Andarahiensis T.D. Penn. e Pouteria Subsessilifolia Cronq. (Sapotaceae) - Carvalho, Monick Lima (2020)
The Sapotaceae family has great relevance in the Brazilian flora, due to the high diversity and well-defined economic and ecological importance. Pouteria is the most representative genus of this family and with the largest number of endemic species. The present study aimed to analyze, using micromorphological and histochemical techniques, the leaves of Pouteria andarahiensis T.D. Penn. and Pouteria subsessilifolia Cronq. endemic to Chapada Diamantina. The analysis of leaf architecture described characteristics that can help in the identification of species in a vegetative state. The leaf surface was analyzed using light microscopy and scanning electron microscopy, presenting unprecedented data for the species, and the cuticle ornamentation suggests adaptations to xeric environments. The transverse cuts made on the leaf blade and on the petiole were made freehand and with a freezing microtome. The anatomy of the leaf blade and petiole showed characters that differentiate the species studied, and are xeromorphic features, with emphasis on the presence of three layers of palisade parenchyma, sclerenchymatous columns in the mesophyll and subepidermal layer of sclerenchyma connecting the vascular bundles in the mesophyll. Histochemical analysis indicated the need for in-depth studies on the composition of the compounds indicated in the present study.